Alternative Splicing for Diseases, Cancers, Drugs, and Databases - Jen-Yang Tang; Jin-Ching Lee; Ming-Feng Hou; Chun-Lin Wang; Chien-Chi Chen; Hurng-Wern Huang; Hsueh-Wei Chang (The Scientific World Journal)
Alternative splicing is a major diversification mechanism in the human transcriptome and proteome. Several diseases, including cancers, have been associated with dysregulation of alternative splicing. Thus, correcting alternative splicing may restore normal cell physiology in patients with these diseases. This paper summarizes several alternative splicing-related diseases, including cancers and their target genes. Since new cancer drugs often target spliceosomes, several clinical drugs and natural products or their synthesized derivatives were analyzed to determine their effects on alternative splicing. Other agents known to have modulating effects on alternative splicing during therapeutic treatment of cancer are also discussed. Several commonly used bioinformatics resources are also summarized.